2021
DOI: 10.1111/jerd.12793
|View full text |Cite
|
Sign up to set email alerts
|

Effect of different surface treatments on optical, colorimetric, and surface characteristics of a lithium disilicate glass–ceramic

Abstract: Objective: To evaluate the effect of surface treatments on optical, colorimetric, and surface characteristics of lithium disilicate glass-ceramic.Materials and Methods: Specimens (n = 5, IPS e.max CAD) were randomly allocated to the following treatments: mirror-polished: SiC papers; as-cut: mimicking CAD-CAM milling; ground: 90-120 μm-grit diamond bur; ground polished: ground, finished (46-30 μm-grit diamond bur), polished (diamond cups, brush and diamond paste); ground glazed: ground, glazed; ground polished … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 41 publications
0
22
0
Order By: Relevance
“…Previous studies have shown that even dental ceramics are prone to color alteration by staining [24][25][26]. However, the color difference can be calculated from other situations that restorative materials are subjected to, such as thermal [21,37] or surface treatments [38]. Even though our conclusions might be cautiously inferred for color difference analyses other than by staining, more studies on this topic (background effect) are encouraged.…”
Section: Discussionmentioning
confidence: 86%
“…Previous studies have shown that even dental ceramics are prone to color alteration by staining [24][25][26]. However, the color difference can be calculated from other situations that restorative materials are subjected to, such as thermal [21,37] or surface treatments [38]. Even though our conclusions might be cautiously inferred for color difference analyses other than by staining, more studies on this topic (background effect) are encouraged.…”
Section: Discussionmentioning
confidence: 86%
“…Weighting functions of S L , S C , and S H are used to adjust the total color difference. The parametric factors ( k L , k C , and k H ) were considered 1 3,18–20 …”
Section: Methodsmentioning
confidence: 99%
“…Surface finishing of glass ceramics usually consists of polishing and/or glazing. [79][80][81][82] After finishing, the surface becomes smoother, which might result in some clinical benefits, such improved esthetics of the restoration and decreased antagonist wear. 83 Both techniques, polishing and glazing, have been the focus of research comparing the surface properties and color stability of glass ceramics before and after different finishing procedures; however, there is not a consensus in the literature concerning the ideal protocol.…”
Section: Glass-matrix Ceramicsmentioning
confidence: 99%
“…83 Both techniques, polishing and glazing, have been the focus of research comparing the surface properties and color stability of glass ceramics before and after different finishing procedures; however, there is not a consensus in the literature concerning the ideal protocol. Most of the studies have indicated that polished surfaces (depending on protocol) results in smoother surfaces than glazed surfaces [79][80][81][82] ; however, glazing might also have a potential improved effect on color stability and flexural strength of glass ceramics. 80 Besides finishing procedures, staining of ceramic restorations might be a useful procedure to improve the mimicking of nuances and shade of natural teeth, especially for monolithic restorations that usually do not meet the high esthetic demands without staining.…”
Section: Glass-matrix Ceramicsmentioning
confidence: 99%
See 1 more Smart Citation